Moon Triggers “Menstrual Clock” - Subba Rao, Y. V. (Advances in Social Sciences Research Journal, 2021)
The study presents that Human Basal Ganglia situated underneath the Human Brain is a plausible reflection of the Solar System wherein the nine celestial bodies are the cosmic counterparts of the nine Basal Nuclei Orders in many aspects such as their orbital location and their significations in astrology of their organization and functions. Moon, the cosmic counterpart of Hypothalamus, together with the other messengers, namely the pituitary gland and the ovary, plausibly regulate human female menstrual cycle. The releasing of hormones by Hypothalamus and its messengers in a rhythmic fashion appear to be the result of variation in the intensity of lunar magnetism. Human females plausibly have an internal ‘menstrual clock’ that helps them anticipate and adapt to the regular rhythm so that it is synchronized with the Moon’s revolutions.